Brazil's landless movement and rights 'from below'. (October 2018) - Hoddy, Eric T.; Ensor, Jonathan E.
Abstract: Recent literature has recognised the value of food sovereignty and human rights frameworks in agrarian struggles. Relatively little attention has gone toward how agrarian movements develop and apply their own rights discourses to further demands for social justice. This study considers Brazil's landless movement (MST) between 1984 and 1995, revealing three distinct rights discourses that recruited and mobilised protest by linking local issues to the movement's broader political project. The findings illustrate the value of rights, frames and ideology as analytical tools, shedding light on how movement-generated rights emerge through processes of reflexivity and in response to dynamic social-political contexts. Highlights: Rights, frames and ideologies help to understand the dynamics of the politics of agrarian change. Three distinct rights discourses of the landless movement used to recruit and mobilise protest. Movement-generated rights emerge reflexively. Movement-generated rights respond to dynamic social-political contexts.